Młodzi kreatywni? Indywidualne strategie zawodowe w (nie)pewnym mieście = Young and creative? Individual career strategies in an (un)certain city - Messyasz, Karolina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper reports on a study conducted among young (up to 35 years old) entrepreneurs from the creative industries, which aimed to create a sociological portrait of OFF Piotrkowska in Lodz as an "enclave of creativity" using the case study method. Seven in-depth individual interviews were used for the analysis. The purpose of the article was to attempt to reconstruct the professional strategies undertaken by the participants, the ways of talking about themselves and their work, and to analyse them as exemplifications of a particular modernization discourse, within which culture is defined as a source of economic and social "profit".
Keywords: kreatywność; Łódź; Lodz; Off Piotrkowska; strategia zawodowa; młodzi przedsiębiorcy; creativity; career strategy; young entrepreneurs